Програма ерготерапії самбістів-ветеранів після лікування травм колінних суглобів - Хацаюк, О. В.; Khatsaiuk, O. V.; Сіренко , Р. Р.; Sirenko, R. R; Русин , Л. П.; Rusyn , L. P.; Ванюк, Д. В.; Vaniuk, D. V.; Беседа , Н. А.; Beseda, N. A.; Кирилюк , В. В.; Kyryliuk, V. V. (Науковий часопис НПУ імені М. П. Драгоманова. Серія 15: Науково-педагогічні проблеми фізичної культури (фізична культура і спорт). - 2023. - Вип. 7(167). - С. 171-179, 2023)
Головною метою дослідження є розроблення програми ерготерапії самбістів-ветеранів після лікування травм колінних суглобів. Методи дослідження: аксіоматичні, ідеалізації, історичні і логічні, сходження від конкретного, формалізації (досвід фізичної терапії, ерготерапії). В результаті емпіричного дослідження розроблено програму ерготерапії самбістів-ветеранів після лікування травм колінних суглобів. Результати емпіричного дослідження впроваджені у систему ерготерапії самбістів-ветеранів. Перспективи подальших досліджень у обраному напрямі наукової розвідки передбачають визначення чинників (факторів), які впливають на довголіття індивіда у обраному виді спортивної боротьби (одноборства).

According to the Results of the analysis of Scientific-Methodical, Special and reference literature by the members of the Scientific Research Group, it was established that insufficient number of Scientific works are devoted to the urgent issue of the organization of the System of Physical Therapy and Occupational Therapy of athletes of older age groups (veterans) who specialize in wrestling (Martial Arts). This emphasizes the relevance and practical component of the chosen direction of Scientific Research. The main goal of the study is to develop an occupational Therapy Program for athletes of older age groups (veterans) who specialize in Sambo wrestling after knee joint injuries. Research Methods: axiomatic, idealization, historical and logical, descent from concrete, formalization (experience of physical Therapy and Occupational Therapy). As a result of an Empirical study, an Occupational Therapy Program was developed for wrestlers of older age groups (Veterans «Masters category») who specialize in Sambo wrestling after knee joint injuries. The Results of the empirical Research are implemented in the System of Physical Therapy of veteran athletes who Specialize in Sports types of wrestling (Judo, Sambo wrestling, Freestyle wrestling, Greco-Roman wrestling). Prospects for further Research in the chosen field of Scientific Research involve the determination of factors that affect the longevity of an individual in the chosen type of sports (combat).

Разработана программа эрготерапии самбистов-ветеранов после лечения травм коленных суставов. Результаты эмпирического исследования внедрены в систему эрготерапии самбистов-ветеранов. Перспективы дальнейших исследований в выбранном направлении научной разведки предполагают определение факторов (факторов), которые влияют на долголетие индивида в избранном виде спортивной борьбы (единоборья).
Occupational Therapy Program for sportsmen (veterans) who specialize in Sambo wrestling of the "Masters" category
Keywords: боротьба самбо; Sambo wrestling; борьба самбо; ветеранський спорт; veteran sport; ветеранский спорт; засоби відновлення; recovery tools; средства восстановления; ерготерапія; occupational therapy; эрготерапия; фізична реабілітація; physical rehabilitation; физическая реабилитация